Reaktualisasi Pemikiran Keagamaan Sjafrudin Prawiranegara (1911-1989) - Hasan Mustapa (JURNAL INDO-ISLAMIKA, 2017)
This paper uncovers that Sjafruddin Prawiranegara (1911-1989), a former charismatic leader of Partai Majelis Syuro Muslimin Indonesia (Masyumi/Council of Indonesian Muslim Associations), makes the normative sources of the Qur’an and Hadith (sayings ascribed to the Prophet Muhammad peace be upon him) actual as primary moral messages to solve a set of social, political, and economic problems in Indonesia. This article depicts this finding by referring to three of his works as the primary resources of this article and to other twenty-nine secondary resources authored by other scholars.